mTORC 2:1 for chemotherapy sensitization in glioblastoma - Wick, Wolfgang; Blaes, Jonas; Weiler, Markus (Cancer discovery, 2011)
mTOR signaling is frequently deregulated in cancer, including brain tumors. Although the signaling of mTOR complex 1 (mTORC1) has been subject to intensive investigations and mTORC1 itself has been a well-established cancer drug target for years, the role of the second complex, mTORC2, remains elusive. Tanaka et al. reveal an EGFRvIII-mTORC2-NFκB signaling cascade and demonstrate that mTORC2 mediates cisplatin resistance through NF-κB in an Akt-independent manner in glioblastoma. Uncovering the role of mTORC2 in chemotherapy resistance in glioblastoma highlights the need for further investigations of mTORC2 inhibition. Cancer Discovery; 1(6); 475-76. ©2011 AACR.Commentary on Tanaka et al., p. 524.